The risks of a “forgetful” linguistics: on the puquina etymology of “inca” - Cerrón-Palomino, Rodolfo (2021)
In this article, I would like to propose the original Puquina affiliation of the name <inca>, a term that was successively adopted by Aymara, Quechua, and Spanish, going through a series of formal and semantic adjustments and readjustments, as a consequence of persistent idiomatic re-accommodations, both spontaneous and deliberate. After offering some background on the subject, my discussion is organized into two detailed sections: in the first, I will offer the etymology of the term in form and meaning, proposing its pristine Puquina affiliation; in the second, I will thoroughly examine and discuss the thesis recently propounded by César Itier (2019), in which he attributes a Quechua origin to the term. I will demonstrate that the proposal put forward by my colleague lacks linguistic and philological support, proving how adherence to the thesis of the so-called “Quechuismo primitivo” (Cerrón-Palomino 2019) can lead to truly unsustainable conclusions not only from a purely linguistic point of view but also, and in a more dramatic way, from its purported interpretative projections regarding the socio-political and organizational Inca institutions.